Marketing Your Medical Laboratory Science Program, a Case Study of Weber State University. - BEAZER, KENDAL (Clinical Laboratory Science)
Laboratories across the United States are having difficulty finding qualified laboratory personnel to fill vacant positions, especially in rural areas. This has forced laboratory administrators to hire employees who lack the proper laboratory training to do the work required and has increased laboratory errors, which poses a risk to patients. An explanation for these shortages is that students are unaware of the profession, or they do not know how to become licensed medical laboratory professionals. After the development of a structured and targeted marketing plan, the Medical Laboratory Science (MLS) program at Weber State University (WSU) experienced significant growth. A regression analysis shows the growth of 27 students per academic year, which equates to roughly 13% yearly increase in matriculation above organic growth. A case study will be presented on WSU's MLS marketing efforts and how it has affected market awareness and matriculation numbers of the program. The targeted marketing plan aims to increase brand awareness and inform the public of the profession. This study characterizes the current online marketing efforts of other MLS departments (including online presence, social media sites, search engines, and links to the program's home page). Marketing strategies are presented that may help individual programs increase market awareness and attract students for greater matriculation numbers.